Determinants of Student Consumer Behavior on the Shopee Online Shopping Platform - Widya Anugrah; Mahmud Mahmud; Sumarni Sumarni (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the determinants of consumer behavior among students at STIE Yapis Dompu regarding their use of the Shopee platform, by examining the influence of lifestyle, financial literacy, and social media. Research Method: This study employs a quantitative, descriptive-associative design. Data were collected using a 5-point Likert scale questionnaire. A sample of 154 active students in the Management Program from the 2022–2025 cohorts was selected using purposive sampling from a population of 706 students, based on the criterion of having made at least two transactions on Shopee. Data analysis was conducted using SEM-PLS with SmartPLS. Results and Discussion: The results indicate that lifestyle and social media positively influence consumer behavior, with social media being the dominant factor. Financial literacy also has a significant influence, but in a direction that does not align with the hypothesis, and thus does not serve as a moderator of consumer behavior in the digital context. Implications: These findings confirm that lifestyle pressures and social media influence the effectiveness of financial literacy. Therefore, financial education needs to be developed in a more context-specific manner, taking into account behavioral aspects and the digital environment.